Effect of proline and Glycine betaine in leaves content of from Auxin , Gibberellic Acid and some antioxidants in orange seedlings of Washington Navel Orange (Citrus sinensis L.) Under Salinity Conditions - Kattab Abdallah, Hayder; Edan Hassan, Alaa; K Abbas, Majeed (Journal of Kerbala for Agricultural Sciences, 2017)
The current experiment was conducted to study the effect of proline and glycine betaine at two concentrations for each; 50 and 100 mM in addition to control and two salts; sodium chloride and calcium chloride at 25 and 50 mM for each in addition to control, in vegetative characters of Washington navel orange (Citrus sinensis L.) grafted on volkamer lemon or swingle citrumelo rootstocks. Salts were added to the irrigation water and seedlings were irrigated with saline water three times at three month interval. After one week of the irrigation with saline water, seedlings were sprayed with the osmoprotectants (three sprays). Treatments were arranged in RCBD design as a factorial experiment(2*5*5)with three replications. The results revealed that the two rootstocks had no effect on the content of the leaves from Auxin , Gibberellic Acid and some antioxidants on swingle citrumelo rootstocks. The use of the two protectants at all concentrations caused significant increase in content of the leaves from Auxin , Gibberellic Acid. Glycine betaine was superior in its effect compare to proline. Also, the two salts had inhibitory effects on most of the parameters measured. The combination between rootstocks and osmoprotectants had significant effect on most growth parameters. In general, most of the two combinations had pronounced effects. In addition, the combination of the three factors also effect the parameters significantly. From the above results, we can conclude that the two salts had an inhibitory effect on the leaves content of Auxin , Gibberellic Acid and some antioxidants which can be improved by the addition of glycine betaine and proline.